Cross-linking affects cellular condensation and chondrogenesis in type II collagen-GAG scaffolds seeded with bone marrow-derived mesenchymal stem cells - Vickers, Scott; Gotterbarm, Tobias; Spector, Myron (Journal of orthopaedic research, 2010)
The formation of cartilaginous tissue by chondroprogenitor cells, whether in vivo or in vitro, appears to require a critical initial stage of “condensation” in which intercellular space is reduced through an aggregation of cells, leading to development of cell-to-cell junctions followed by chondrocytic differentiation. The objective of this study was to investigate the association of aggregation (condensation) of mesenchymal stem cell (MSCs) and chondrogenesis in vitro.